2018
DOI: 10.1017/s175173111800023x
|View full text |Cite
|
Sign up to set email alerts
|

Pedigree analysis and inbreeding effects over morphological traits in Campolina horse population

Abstract: Genetic improvement, without control of inbreeding, can go to loss of genetic variability, reducing the potential for genetic gains in the domestic populations. The aim of this study was to analyze the population structure and the inbreeding depression in Campolina horses. Phenotype information from 43 465 individuals was analyzed, data provided by the Campolina Breeders Association. A pedigree file containing 107 951 horses was used to connected the phenotyped individuals. The inbreeding coefficient was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…In this study, we reported the presence of significant inbreeding effect in height at withers only, whilst all remaining traits were not affected by inbreeding. This finding agrees with previous studies where inbreeding mainly impacted morphological features rather than complex traits (Bussiman et al, 2018;Curik et al, 2003;Gómez, Valera, Molina, Gutiérrez, & Goyache, 2009;Klemetsdal, 1998;Vicente et al, 2014).…”
Section: Scoring Systemsupporting
confidence: 93%
“…In this study, we reported the presence of significant inbreeding effect in height at withers only, whilst all remaining traits were not affected by inbreeding. This finding agrees with previous studies where inbreeding mainly impacted morphological features rather than complex traits (Bussiman et al, 2018;Curik et al, 2003;Gómez, Valera, Molina, Gutiérrez, & Goyache, 2009;Klemetsdal, 1998;Vicente et al, 2014).…”
Section: Scoring Systemsupporting
confidence: 93%
“…The f e /f a ratio found in this study was 1.74, which indicates a decrease in genetic variability caused by an unequal founder contribution, i.e., some breeding animals become popular and produce more progeny than others. This has also been seen in other horse breeds, such as the Campolina horse population [35] with an f e /f a ratio of 1.51, the Spanish Arab Horse [25] with a ratio of 2.03% or in the Old Kladruber horse with a ratio of 5.40 [26].…”
Section: Discussionmentioning
confidence: 54%
“…Approximately 45% of all pedigreed animals presented some level of inbreeding. The mean inbreeding coefficient was 5.64% for the inbreds and 2.45% when considering the complete population (a more detailed description of this population can be found in Bussiman et al, 2018).…”
Section: Available Datamentioning
confidence: 99%